Does Goat weed and Scent leaf meals Influences Gr owth performance, Blood indices, Carcass traits and Gut Microbiota of broiler chicken? - Obakanurhe, O; Aberji, OD; Onwumere-Idolo, OS; Gbayisomore, OS (Journal of the Hellenic Veterinary Medical Society, 2025)
The search for a safer antibiotic of phytogenic origin using Goat weed leaf meal and Scent leaf meal as additive was investigated on 240 unsex day old chicks of Ross 308 strain. The birds were allotted into six diets and replicate four times with 10 birds per replicate in a completely randomized design. D1 was the control, D2 had 10g of Antibiotics (Diaziprim-48% S), while D3-D6 have 0.6g + 0.6g, 0.9 + 0.9g, 1.2 + 1.2g and 1.5 + 1.5g (GWLM + SLM) per kg of the feed respectively. At 21 days old, D4 recorded significant values of 1116.22g on final weight, 1076.02g weight gains, 1544.06g feed intake and better feed conversion ratio of 1.43. The birds final weight (2571.35g) and weight gain (1462.35g) on D5 at 42days was significantly (p>0.05) different compared to the other diets. The result on feed intake revealed that D1 and D5 had superior (2607.45g) and least (2565.44g) value. The feed conversion ratio of birds showed significantly better value on D5 in comparison to other diets. Also, the additives affected the cost of diets and cost of weight gain of the birds across the diets. The result on haematology and serum biochemistry revealed significant differences on WBC where D5 and D6 recorded superior values compared to other treatments. The blood indices of the birds revealed no adverse effects cause by the diets. The results on AST and ALT recorded decrease values with higher supplementation of the additives. The MDA, SOD, T-AOC, GSH-Px and CAT were within the range of healthy birds. The microbial load of birds revealed a reduced microbial load of Staphylococcus spp, Escherichia coli and Salmonella were observed at higher inclusion of the additives. In conclusion, adding these additives in the diets of broiler chickens could enhance the growth performance as reflected on the blood profile, carcass qualities, oxidative status and the reduce microbial loads without any adverse effects on the birds.